Comparative analysis of gut DNA viromes in wild and captive Himalayan vultures - Zhai, Jundie; Wang, You; Tang, Boyu; Zheng, Sisi; He, Shunfu; Zhao, Wenxin; Chen, Hanxi; Lin, Jun; Li, Feng; Bao, Yuzi; Lancuo, Zhuoma; Sharshov, Kirill; et al. (Frontiers in Microbiology, 2023)
Introduction: Himalayan vultures (Gyps hinalayensis) are widely distributed on the Qinghai-Tibetan Plateau and play a crucial role in maintaining the ecological balance by feeding on decayed corpses of wild and domestic animals. Large-scale culture and metagenomics studies have broadened our understanding of viral diversity in animals' gastrointestinal tracts. However, despite the importance of gut viral communities in regulating bacterial diversity and performing symbiotic functions, no gut viral study has been conducted on Himalayan vultures. Furthermore, the impact of captivity on the gut virome of these vultures remains unknown.In this study, metagenomic sequencing methods targeting DNA of virus-like particles enriched from feces were used to characterize the gut DNA viromes of wild and captive Himalayan vultures.Results: In total, 22,938 unique viral operational taxonomic units (vOTUs) were identified and assigned to 140 viral genera in 41 viral families. These families included viruses associated with bacteria, animals, plants, insects, and archaea. Phage communities, including Siphoviridae, Microviridae, Myoviridae, Inoviridae, and Herelleviridae, dominated the gut virome of Himalayan 2 This is a provisional file, not the final typeset article vultures. Wild vultures exhibited higher viral richness and diversity compared with those in captivity. The functional capacity of the gut virome was characterized by identifying 93 KEGG pathways, which were significantly enriched in metabolism and genetic information processing. Abundant auxiliary metabolic genes, such as carbohydrate-active enzyme, and antibiotic resistance genes, were also found in the vultures' gut virome.Discussion: Our findings reveal the complex and diverse viral community present in the gut virome of Himalayan vultures, which varies between wild, and captive states. The DNA virome dataset establishes a baseline for the vultures' gut virome and will serve as a reference for future virus isolation and cultivation. Understanding the impact of captivity on the gut virome contributes to our knowledge of vultures' response to captivity and aids in optimizing their rehabilitation and implementing protective measures.